A Review of Rubrics in Education: Potential and Challenges - Jen Hua Ling (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: In recent years, the use of rubrics in educational assessment has gained significant attention due to their potential to enhance transparency, consistency, and learning outcomes. However, debates persist regarding their practical implementation, effectiveness, and limitations in various educational contexts. Objective: This study reviews the literature on rubrics, focusing on their role in learning facilitation, fair assessment, reliability, and validity. Method: The research follows a literature study approach, analyzing data from journals, scientific articles, and literature reviews. The analysis process includes data collection, classification, presentation, and conclusion drawing, with data triangulation used for validation. Results: Teachers should have the flexibility to decide whether to use rubrics. If adopted, rubrics must be well-designed and implemented by incorporating essential characteristics, avoiding common pitfalls, and continuously improving them to ensure fairness, reliability, and validity. Conclusion: Rubrics can be effective assessment tools when properly designed and implemented, but they require ongoing refinement to maximize their benefits. Contribution: This study provides insights into best practices for rubric use, highlighting key factors for effective implementation in educational settings.